Key account management : the definitive guide - Woodburn, Diana; McDonald, Malcolm (Chichester, West Sussex, U.K. : Wiley, 2011)
'This helpful text clearly sets out the very best, state-of-the-art strategies in key account management. The authors provide the tools and processes for successful KAM, from developing a customer categorization system that really works, to analyzing the needs of key accounts. Topics include why key account management has become so critical to commercial success; the role of key management in strategic planning; how companies build profitable relationships with their customers; and what it takes to be a successful key account manager.'--
'This helpful text clearly sets out the very best, state-of-the-art strategies in key account management. The authors provide the tools and processes for successful KAM, from developing a customer categorization system that really works, to analyzing the needs of key accounts. Topics include why key account management has become so critical to commercial success; the role of key management in strategic planning; how companies build profitable relationships with their customers; and what it takes to be a successful key account manager'--
Includes bibliographical references and index.
Keywords: Selling -- Key accounts; Marketing -- Key accounts